The Influence of Platinum Dopant on the Characteristics of SnO2Thin Film for Gas Sensor Application - T. Sujitno; Sudjatmoko Sudjatmoko (Atom Indonesia, 2006)
Doping of platinum on tin dioxide (SnO2) thin film for gas sensor application has been carried out using ion implantation techniques. The SnO2 thin film has been deposited using dc sputtering method at the conditions; operating pressure 5x10-2 torr, anode-cathode voltage 2.0 kV, substrate temperature 2000C and deposition time one hour. While the Pt ion implantation process were carried out at energy 60 keV and ion doses were varied.  From scanning electron microscope (SEM) observation, it was found that   SnO2:Pt thin film which was deposited by those parameters has a fine morphology with the grain size of thin film was in order of 0.7 – 1.0 μm and thickness 4.16 μm.  From crystal structure analysis using XRD it was observed that the crystal planes of SnO2:Pt were  (110), (101), (200), (211), (300), and (112) . From energy dispersive X-rays analysis (EDX) coupled with SEM, it was found that the chemical composition of SnO2:Pt  thin film were 66.12%-at O, 1.23 %-at Si, 0.12 %-at Pt and 32.53 %-at Sn.  It was also found that the influence of platinum dopant on SnO2 thin film can reduce significantly the resistance of thin film and from response time and sensitivities measurement showed that for every dose variation for different tested gas has a different respons time and sensitivities (no a specific pattern)